Sponsors' and investigative staffs' perceptions of the current investigational new drug safety reporting process in oncology trials. (June 2017) - Perez, Raymond; Archdeacon, Patrick; Roach, Nancy; Goodwin, Robert; Jarow, Jonathan; Stuccio, Nina; Forrest, Annemarie
Background/aims: The Food and Drug Administration's final rule on investigational new drug application safety reporting, effective from 28 March 2011, clarified the reporting requirements for serious and unexpected suspected adverse reactions occurring in clinical trials. The Clinical Trials Transformation Initiative released recommendations in 2013 to assist implementation of the final rule; however, anecdotal reports and data from a Food and Drug Administration audit indicated that a majority of reports being submitted were still uninformative and did not result in actionable changes. Clinical Trials Transformation Initiative investigated remaining barriers and potential solutions to full implementation of the final rule by polling and interviewing investigators, clinical research staff, and sponsors. Methods: In an opinion-gathering effort, two discrete online surveys designed to assess challenges and motivations related to management of expedited (7- to 15-day) investigational new drug safety reporting processes in oncology trials were developed and distributed to two populations: investigators/clinical research staff and sponsors. Data were collected for approximately 1 year. Twenty-hour-long interviews were also conducted with Clinical Trials Transformation Initiative–nominated interview participants who were considered as having extensive knowledge of and experience with the topic. Interviewees included 13 principal investigators/study managers/research team members and 7 directors/vice presidents of pharmacovigilance operations from 5 large global pharmaceutical companies. Results: The investigative site's responses indicate that too many individual reports are still being submitted, which are time-consuming to process and provide little value for patient safety assessments or for informing actionable changes. Fewer but higher quality reports would be more useful, and the investigator and staff would benefit from sponsors'"filtering" of reports and increased sponsor communication. Sponsors replied that their greatest challenges include (1) lack of global harmonization in reporting rules, (2) determining causality, and (3) fear of regulatory repercussions. Interaction with the Food and Drug Administration has helped improve sponsors' adherence to the final rule, and sponsors would benefit from increased communication with the Food and Drug Administration and educational materials. Conclusion: The goal of the final rule is to minimize uninformative safety reports so that important safety signals can be captured and communicated early enough in a clinical program to make changes that help ensure patient safety. Investigative staff and sponsors acknowledge that the rule has not been fully implemented although they agree with the intention. Clinical Trials Transformation Initiative will use the results from the surveys and interviews to develop new recommendations and educational materials that will be available to sponsors to increase compliance with the final rule and facilitate discussion between sponsors, investigators, and Food and Drug Administration representatives.